Divergence of Safety and Security - Brooks, David J. (2020)
© 2020, The Author(s). Safety and security have similar goals, to provide social wellness through risk control. Such similarity has led to views of professional convergence; however, the professions of safety and security are distinct. Distinction arises from variances in concept definition, risk drivers, body of knowledge, and professional practice. This chapter explored the professional synergies and tensions between safety and security professionals, using task-related bodies of knowledge. Findings suggest that safety and security only have commonalities at the overarching abstract level. Common knowledge does exist with categories of risk management and control; however, differences are explicit. In safety, risk management focuses on hazards management, whereas security focuses on threat mitigation. Safety theories consider health impacts and accidents, whereas security crime and crime prevention. Therefore, safety and security are diverging as distinct professions